Fuzzy Control for Optimizing Ship Tracking in Karang Jamuang – Tanjung Perak - A. Masroeri; Mohamad Aries Efendi; Eko B. Djatmiko; Wasis D. Aryawan; Fitri A. Iskandarianto (IPTEK The Journal for Technology and Science, 2012)
Karang Jamuang West Track - Tanjung Perak is one of the busiest routes for sea transportation in Indonesia. This paper proposes an attempt to optimize the ship’s trajectory by designing a track keeping control along that track line. Control system is designed based on fuzzy logic (FLC). FLC design intended to control the speed and the bow of the ship in order to keep the track. FLC 1 control the speed of the input changing by the distance, while the FLC 2 control the prow with yaw angle and yawrate error input. As an object for autopilot is Brotojoyo MT tanker. The research was done by simulation, and generate the ability of FLC which able to keep the track with small error